Lazaro Francisco the making of a national artist - Reyes, Soledad S. (2019)
This essay situates the novels of Lazaro Francisco against the concrete specificities of our history as a nation, from the American colonial regime to the postwar period. The study shows how deeply Francisco the concept of nationhood even as he constructed experiences of socio-economic bondage and a disastrous war that resonated with his Liwayway readers.
Keywords: Tagalog novel; Philippine literary history; National Artist for Literature; Francisco, Lazaro A